Pr??tica motivacional de compartilhamento do conhecimento organizacional em portais corporativos - Mendes, S??rgio Peixoto (2004)
In the current context of the age of knowledge one of the biggest challenges faced for the organizations it is to manage the tacit knowledge. Some unsatisfactory initiatives have presented resulted and the returns of the investments have not been the waited one for the organizations. To manage the knowledge is basic to keep the competitiveness in a market each more demanding time, where, to add new values to the product it depends, basically, of an efficient management of the intellectual assets. But, as to manage the knowledge that is in the head of the people? How to motivate them it the sharing? To answer to these questions, the study it understood a supported theoretical referencial in management of the knowledge, internal marketing and corporative vestibules. The quantitative, descriptive research and of field was carried through in the SERPRO and counted on the opinion of 55 managers of the knowledge. The result was the identification of the necessary subsidies for elaboration of programs that allow to measure and to implement practical of recognition and rewards aiming at to to improve sharing of the enterprise knowledge. One presents a proposal for the construction of strategical and operational a panel of pointers, making possible the application of objective criteria in the awarding process and rewards. It is concluded that only the existence of a corporative vestibule is not condition enough to guarantee the sharing of the enterprise knowledge, is necessary to develop practical adjusted motivations, together to its picture of collaborators, so that the tacit knowledge can be shared in corporative vestibules.